2009
DOI: 10.1063/1.3220173
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional instabilities and transient growth of a counter-rotating vortex pair

Abstract: International audienceThis paper investigates the three-dimensional instabilities and the transient growth of perturbations on a counter-rotating vortex pair. The two dimensional base flow is obtained by a direct numerical simulation initialized by two Lamb-Oseen vortices that quickly adjust to a flow with elliptic vortices. In the present study, the Reynolds number,ReΓ=Γ/ν, with Γ the circulation of one vortex and ν the kinematic viscosity, is taken large enough for the quasi steady assumption to be valid. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 37 publications
7
49
1
1
Order By: Relevance
“…(For time-dependent equations, this can be directly shown by taking the adjoint of the propagator as given in equation (4) of Farrell & Ioannou 1996.) It is straightforward to establish (see for example Hill 1995;Donnadieu et al 2009) that the adjoint equations of (2.1) are…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…(For time-dependent equations, this can be directly shown by taking the adjoint of the propagator as given in equation (4) of Farrell & Ioannou 1996.) It is straightforward to establish (see for example Hill 1995;Donnadieu et al 2009) that the adjoint equations of (2.1) are…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Throughout this paper we will set the central flow parameter Re = 1000 (except in § 5.4, where we study the effect of variations in Re), which is sufficiently large to ensure that the primary instability rolls up into a finite-amplitude, energetic billow. These adjoint equations can be solved using a straightforward modification of a pseudo-spectral DNS code with an Adams-Bashforth time scheme (as previously described and utilized by Donnadieu et al 2009). In particular, the central point arising from the integration by parts that the Laplacian operator has an opposite sign (and hence that the adjoint propagator is well-posed when integrating backward in time) is very simple to implement computationally.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] It has been theoretically shown that three-dimensional instabilities may grow in a counter-rotating vortex pair. 17 The aims of this experimental study are to investigate the interactions between a pair of jets, emanating from the upswept face of a simplified fuselage model, and the afterbody vortex pair, and to understand how these interactions are affected by the blowing location and direction. This is compared against the baseline flow field (without blowing).…”
Section: Introductionmentioning
confidence: 99%
“…Thin arrowed lines in (a) and (d) represent streamlines of the optimal perturbation and its outcome, respectively. (Moore & Saffman 1975;Donnadieu et al 2009). In the absence of axial base flow as in the present case, the elliptic instability was reported to be dominant over the curvature instability in a vortex ring flow (Blanco-Rodríguez & Le Dizèz 2016a,b).…”
Section: The Orr Mechanismmentioning
confidence: 99%